Consommation De Boissons Desalterantes Et Risques Sanitaires Dans Les Colleges De La Ville D’abomey (Republique Du Benin) - V. B. Fanès Azalou Tingbe; Thierry Hervé Azonhe; Alda Yemadje; Armand Arnaud Vido (European Scientific Journal, ESJ, 2018)
This research aims to analyze the health quality of thirst-quenching drinks such as fruit juices produced, sold and consumed in schools. The research was conducted on a sample of 222 learners selected in a classroom setting plus 6 randomly selected female sales representatives in schools. The microbiological analyzes were carried out on samples of different juice drinks made in the colleges. Digitization of collected data, descriptive statistics, cross tables, chi-2 tests, etc. are the statistical tools used. The results show a significant consumption of thirst-quenching drinks: hibiscus flower juice (39.2 %), water (24.1 %), fruit juice (21.6 %), local beer-based cereals (tchakpalo), 12.8% in CEG 1 and 2 of the city of Abomey. The main reasons for their consumption are related to the need for quenching, the presence of sugar and aroma in these drinks and their almost daily availability. As for the microbiological analyzes, they show a contamination of the juice units taken with a significant difference between total flora, molds, yeasts, staphylococci, etc. The contamination factors are related to the quality of the products as well as to the process of making beverages and the hygiene of the houses. Measures to improve hygiene education and improve production techniques are needed to limit the health risks of these thirst-quenching drinks.